ROBOTIC STEREO EEG IN EPILEPSY SURGERY ASSESSMENT. Issue 11 (9th October 2013) - Sieradzan, Katarzyna; Sandeman, David; Smith, Shelagh; Trippick, Kathy; Johnson, Claire
Abstract : Epilepsy surgery remains the only chance of becoming seizure–free for many patients with focal epilepsies refractory to medical treatment. In those cases where plan of surgery cannot be formulated on the basis of non–invasive studies (MRI, scalp videotelemetry, neuropsycholgy, CT PET, MEG), intracranial EEG (ICEEG) recording can often identify seizure onset zone and make surgery possible. In the UK, the most commonly used ICEEG technique is implantation of subdural grids/strips+depth electrodes, the latter usually implanted into the mesial temporal structures. Until recently electrocorticography using subdural grids/strips combined with mesial temporal depth electrodes was routinely used in our centre. Since November 2011 we have switched to stereoEEG (sEEG) technique with robotic stereotactic implantation of multiple depth electrodes using Renishaw Neuromate robot. So far we have carried out sEEG implantation in 11 cases. The indications for sEEG included: Non–lesional TLE (n=4) Focal cortical dysplasia in proximity to eloquent cortex, e.g. L frontal lobe close to the motor strip or parietal lobe close to the primary sensory cortex (n=2) Dual pathology (n=1) Multiple lesions (tuberous sclerosis) (n=1) Bitemporal epilepsy (n=1) Re–investigation of previous unsuccessful resection (n=2) SEEG identified seizure onset zone in 10/11 of patients. In 1 patient (tuberous sclerosis with multiple tubers) ICEEG data were not sufficient to proceed to surgery and further studies are pending. Seven patients have undergone surgery and 3 patients are awaiting surgery. Seizure–free (Engel I) outcome has been seen in 5/7 patients who had surgery (follow up period 5–14 months, mean 9.8 months). In one case of bitemporal epilepsy (80% seizures originating in one temporal lobe and associated with ictal asystole), where surgery was undertaken with palliative intent, Engel III outcome has been seen. In 1 case only subjective events have been reported (possible non–epileptic attacks, awaiting further evaluation). No surgical complications of sEEG have been seen. The procedure is very well tolerated. The average time of recording (including stimulation studies) has been 9 days. Robotic sEEG has been a safe intracranial EEG technique that permits exploration of remote/ discontinuous brain regions and, importantly, the deep structures not accessible to subdural grid recording. Its advantages include: no need for craniotomy well tolerated by patients low risk of infection and bleeding complications electrodes can be removed and surgery planned electively at a later date it can be carried out in patients with history of previous subdural grid implantation/ neurosurgery The disadvantages are that cortical stimulation studies may be more limited (relative disadvantage) and the need for specialised equipment (expense).